Analisis Penggunaan Diksi dalam Berita CNN Indonesia Edisi 2025–2026: Kajian Diksi Gerys Keraf - Andini Aulia Distira; Poppy Adelia Adisty; Ines Amelia; Aulia Uswatun Siagian; Jakaria Jakaria (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
This research is motivated by the importance of the appropriate use of diction in online news which influences the clarity and understanding of information by readers. This study aims to analyze the use of diction in CNN Indonesia news edition 2025–2026 based on Gorys Keraf's diction theory study. The research method used is descriptive qualitative with content analysis techniques. The research data was taken from three CNN Indonesia news articles, namely